Тарас Шевченко про чумацтво, його звичаї та пісні - Яременко, В. (Народна творчість та етнографія, 2005)
Traveling Waggoner was one of the most important and prestige work of the Ukrainians at particular historical times. In the T. Shevchenko heritage these people got a lot of attention in both literature texts and paintings. The author of this article gives the deep analysis of the philosophical and historical origins of the Wagoner motifs in Shevchenko's art. T. Shevchenko brought the knowledge about Waggoner gob and life style from an early childhood. His ethnographical descriptions of a life style of such people correspond completely to an official information about Waggoners. T. Shevchenko's art is a miniature reflection of the traveling Waggoners life (social and ethnographical). The scrupulous analyses of the poetry and paintings with the "Chumatsky" motif i testifies that there are a strong connection with the history, philosophy and social life of this social group of Ukrainian population. T. Shevchenko's poetry shows a link between unhappy imperial life of the contemporaries and the Cossacks liberty. The Traveling Waggoners became in his poetry the symbolic figure representing Ukrainians who are trying to remember their historical, religious and ethnic heritage but their consciousness has had some deformation. This aspect gives an additional element for Shevchenko's myth of Ukraine.